INNOVATIVE TECHNOLOGIES IN ALZHEIMER’S DISEASE MANAGEMENT: A COMPREHENSIVE REVIEW OF DIAGNOSTIC AI, VIRTUAL REALITY INTERVENTIONS, AND WEARABLE MONITORING SYSTEMS - Radosław Swędrak; Marzena Swojnóg; Zuzanna Dobrakowska; Jakub Klepacz (International Journal of Innovative Technologies in Social Science, 2026)
Alzheimer’s Disease (AD) constitutes one of the most critical public health challenges of the 21st century, imposing an immense socioeconomic burden on global healthcare systems. As pharmacological treatments remain limited, there is a paradigm shift towards integrating digital health solutions into the continuum of care. This review article synthesizes recent advancements (2019–2025) across the full spectrum of assistive technologies: from Artificial Intelligence (AI) algorithms for early diagnosis and predictive analytics, through Virtual Reality (VR) and Socially Assistive Robotics (SAR) for non-pharmacological therapy, to Wearable IoT ecosystems for patient safety. Furthermore, the review expands the scope to the macro-level, analyzing the economic impact of these innovations and the role of Smart Cities in creating dementia-friendly environments. The findings indicate that while digital phenotypes and remote monitoring offer superior precision and can significantly reduce caregiver burden, their widespread adoption is hindered by the "digital divide," ethical concerns regarding privacy, and reimbursement gaps. The paper concludes that the future of AD management lies in a hybrid "High-Tech, High-Touch" model that balances technological efficiency with human empathy.